Advanced Techniques for Glucose Oxidase Immobilization: Evolution, Computational Integration, and Biomedical Applications - G Sreenivasulu; R. Ramakoteswara Rao (Advances in Engineering and Intelligence Systems)
Glucose oxidase is a crucial enzyme used in industries such as chemicals, pharmaceuticals, food, and biotechnology due to its ability to oxidize glucose into hydrogen peroxide and gluconic acid (C6H12O7). However, its limited and costly production necessitates strategies for improved efficiency. Immobilization, which involves attaching enzymes to surfaces, is a key method that enhances glucose oxidase's activity, stability, and reusability, making it more practical for repeated industrial use. This study comprehensively reviews glucose oxidase immobilization techniques, emphasizing their evolution, advanced methods, and diverse applications, particularly in biomedical fields. By immobilizing glucose oxidase, its stability, activity, and reusability are significantly enhanced, addressing the challenges of enzyme production and operational efficiency. The review discusses various immobilization methods, including physical adsorption, covalent binding, entrapment, and encapsulation, comparing their advantages and limitations. Incorporating nanomaterials and computational methods, such as molecular modeling and simulations, further optimizes the immobilization process, providing insights into enzyme-support interactions and improving performance in applications like biosensors, biofuel cells, and drug delivery systems. The study also explores future trends, including artificial intelligence and innovative support materials, to drive advancements in glucose oxidase immobilization. By integrating these techniques, the study aims to pave the way for more effective and versatile biomedical solutions, contributing to the ongoing evolution of enzyme immobilization technology.